Caught in the Middle? The Economics of Middle-Income Traps - Pierre-Richard Agenor (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
This paper provides an overview of the recent analytical and empirical literature on middle-income traps. The first part examines the descriptive and statistical evidence on these traps. The second discusses the various arguments that have been put forward to explain the existence, and persistence, of middle-income traps. These arguments include diminishing returns to physical capital, exhaustion of cheap labor and imitation gains, insufficient quality of human capital, inadequate contract enforcement and intellectual property protection, distorted incentives and misallocation of talent, lack of access to advanced infrastructure, and lack of access to finance, especially in the form of venture capital. The third part considers public policies aimed at avoiding, and escaping from, middle-income traps. The concluding part identifies a number of directions in which the empirical and theoretical literature could fruitfully evolve.
Keywords: H54; O31; O41; 330